Celebrating 25 Years of Optical Biometry: A Milestone in Ophthalmology - Scholtz, Sibylle Katharina; Langenbucher, Achim; Stachs, Oliver (Klinische Monatsblätter für Augenheilkunde, 2024)
Optical biometry has fundamentally transformed cataract surgery, and 2024 marked 25 years since the introduction of the first optical biometer. In the early 1980 s, Fercher and colleagues pioneered the optical noncontact eye length measurement, leading to the first interferometric A-scan of the eye. This innovation, patented and later developed by Zeiss, culminated in the release of the IOLMaster in 1999, enabling more accurate and reproducible eye diagnostics. Over the years, optical biometry has evolved into advanced swept-source optical coherence tomography devices, accompanied by numerous formulas for calculating intraocular lens power. Today, this technology is crucial not only for cataract surgeries, especially in eyes previously treated with refractive surgery, but also in advancing our understanding of diseases across fields like cardiology and oncology.
Keywords: cataract surgery; optical biometry; optical coherence tomography; IOL calculation